The Development Strategy of Wingko Agroindustry (Case Study: Ud. Bintang Jaya In Lamongan Regency) - Elif Putri Anggraini; Nuriah Yuliati; Nisa Hafi Idhoh Fitriana (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Lamongan Regency is a wingko production center area which shows that many wingko agro-industries are developing. This results in increased competitiveness and market expansion between agro-industry. Therefore, this research aims to identify and analyze internal and external environmental factors and formulate a development strategy for the wingko agroindustry at UD. Bintang Jaya, Babat District, Lamongan Regency. The data analysis method used in this research is quantitative descriptive, including stages of data processing and descriptive data interpretation. The data obtained came from interviews and observations. This research was conducted from December 2023 to March 2024. The analysis used consisted of SWOT (Strength, Weakness, Opportunities, Threats) analysis and QSPM (Quantitative Strategic Planning Matrix) analysis. The research results show that based on the SWOT analysis, the Wingko UD agro-industry. Bintang Jaya has an IFAS score of 2.89 and an EFAS score of 2.68, placing it in quadrant V (growth) with significant potential for development. The external internal matrix is in the white area, suggesting the implementation of an S-O (Strengths-Opportunities) strategy. The recommended S-O strategy includes increasing production volume and maintaining raw material availability, as well as improving product quality and innovating new products with variations in taste and size. QSPM analysis shows that the priority strategy is improving product quality and new product innovation with a Total Attractiveness Score value of 5.92. Thus, product innovation is expected to improve the performance and productivity of Wingko UD's agro-industry. Bintang Jaya, opens up opportunities to increase the profits and competitiveness of the wingko agro-industry as a whole.Keywords: wingko agroindustry, development strategy, SWOT, QSPM.